THE ANALYSIS OF CONSUMER BEHAVIOR OF MILLENNIALS AND Z GENERATION TRAVELING IN JAPAN DURING THE COVID-19 PANDEMIC - Asep Parantika (Universitas Terbuka, 2021)
The study aims to analyze the consumer behavior of domestic travelers in Japan, especially the Millennial and Z generation groups during the Covid-19 pandemic. Fears of exposure and the imposition of a state of emergency, making tourists both domestic and foreign cancel their trips. Economic downturn amid the threat of the spread of a pandemic that is not yet known when it will end, it becomes a challenge for Japanese society to adjust to existing conditions. The Japanese government issued the